Internal curing of high performance concrete using lightweight and recycled aggregates - Afifi, Mohamed (AUC Knowledge Fountain, 2016)
Concrete curing is of paramount importance in order for concrete to meet performance requirements. Conventionally, curing has been conducted by means of water sparkling, wet burlap or a curing compound. For performance and environmental reasons, internal curing has been gaining increased attention. However, more data is needed for the effectiveness of this curing technique when used in various concrete mixtures. This investigation addresses potential utilization of internal curing in high performance concrete (HPC). Internal curing was introduced by means of three aggregates: perlite, pumice and recycled aggregates; all of which were incorporated into HPC mixtures. Conventional mixtures were prepared and were thoroughly cured either by water or by a curing compound or left non-cured. Fresh concrete and Hardened concrete properties were assessed including slump, unit weight, compressive and flexural strength, and durability tests as shrinkage assessment, rapid chloride permeability test (RCPT) and abrasion resistance. Experimental work is backed up with a simplified feasibility analysis with case study, incorporating initial and future costs to better judge potential of this technique. The outcome of this study uncovers that the addition of pre-wetted lightweight aggregates can prompt an enhancement in concrete workability and durability accompanied by a reduced shrinkage. Compressive and flexural strengths decreased with the increased replacement dosages, however several dosages were tested to reach a figure of optimum replacement. Results of this study reveal the potential of this technology in saving fresh water as well as the costs saved in maintenance and rehabilitation works.